Empirical likelihood ratio under infinite covariance matrix of the random vectors. Issue 18 (20th August 2021) - Cheng, Conghua; Liu, Zhi
Abstract: In this article, we show that the log empirical likelihood ratio statistic for the population mean vector converges in distribution to χ ( q ) 2 as n → ∞ when the population is in the domain of attraction of normal law but has infinite covariance matrix. The simulation results show that the empirical likelihood ratio method is applicable under the infinite second moment condition.